The culinary technical aspect in the categorization of restaurants and consumer behavior in Nueva Loja, Ecuador - Quintana Lombeida, María Dolores (2022)
In this study, the culinary technical aspect is analyzed in order to know the influence on the allocation of the category and on the buyer’s behavior in the course of the purchase decision. For this purpose, the legal regulations of restaurants and the study of the gastronomic market linked to marketing tools are taken into account. This research is of a qualitative-exploratory type, applied to food and beverage establishments in Nueva Loja, Ecuador; direct observation, culinary technical questionnaires for restaurants and consumer interviews are used. From the individual evaluation, the current level of efficiency of each establishment and the consumers’ perception of the quality of the gastronomic offer are determined. The results identify that more than half of the establishments in different categories are not very efficient, which has a negative influence on the perception of demand in Nueva Loja’s gastronomic market.